OMEGA-3 POLYUNSATURATED FATTY ACIDS AND COGNITIVE DEVELOPMENT OF CHILDREN - O. A. Gromova; I. Yu. Torshin; Ye. Yu. Yegorova ("Paediatrician" Publishers LLC, 2011)
Omega-3 polyunsaturated fatty acids (PUFA) are important nutrient for proper support of normal living. Omega-3 PUFA play significant role in neurogenesis, neurotransmission, neuroprotection, they are necessary for development of human's brain. Present study discusses results of fundamental and clinical studies on role of omega-3 PUFA in ontogenesis. Authors performed systematic analysis of physiological effects of omega-3 PUFA on molecular level. Deficiency of omega-3 PUFA results in decrease of intellect and increase of hyperactivity in children. The necessity of proper administration of omega-3 PUFA in early pre-school period and in younger schoolchildren is confirmed by results of clinical studies.